Reading Test Construction of Efl Teachers In Islamic Senior High Schools - Santri, Fadilah (IAIN Parepare, 2023)
This study aims to describe the process of constructing reading test conducted by English teachers from various Islamic high school at Binuang. This study used a qualitative approach with a descriptive research design. The subjects in this study were six English teachers from different Islamic High Schools at Binuang District, West Sulawesi. The instruments in this study were the researchers herself and were assisted through data collection tools namely interview guides and documentation. Data analysis begins with data collection then reduced and categorized, data presentation and concluded. The findings showed that there are five steps that English teachers go through in constructing good reading tests. This step was developed from theory (Brown 2004; Sharma, 2017 & Suwarto, 2017) namely starting from the planning stage, writing test items, standardization tests, revising and interpreting test results or scoring